Pemberian Terapi Genggam Bola Karet Ball Squeezing pada Pasien Stroke Nonhemoragik dengan Masalah Keperawatan Gangguan Mobilitas Fisik - Yuliani Yuliani; Ida Ayu Agung Laksmi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Non-hemorrhagic stroke occurs due to blockage of blood flow to the brain by a thrombus or embolus. The blockage results in focal neurological disorders that affect the musculoskeletal system, namely weakness in the extremities, which gives rise to nursing problems of impaired physical mobility. To overcome the problem of impaired physical mobility, rubber ball grip exercises (ball squeezing) are given. These exercises have been shown to increase muscle strength, prevent joint stiffness, and improve blood circulation. This scientific paper was conducted to determine the description of nursing care for non-hemorrhagic stroke patients with nursing problems of impaired physical mobility. During the meeting, the nurse provided rubber ball grip exercises (ball squeezing) for 10-15 minutes for 3 times in 24 hours. Evaluation of these actions showed that the patient who initially experienced weakness in the upper extremities with muscle strength 2-3 and after being given rubber ball grip exercises (ball squeezing), the problem of impaired physical mobility was resolved, as evidenced by the patient being able to perform therapy, the extremities feeling slightly lighter, and muscle strength 4. Therefore, it is recommended that non-hemorrhagic stroke patients be given rubber ball grip exercises (ball squeezing) to overcome impaired physical mobility.